4(x + 3) = 6 - x
First, expand to remove parentheses.
Second, subtract '6' from both sides.
Third, subtract '12 - 6' to get 6.
Fourth, subtract '4x' from both sides.
Fifth, since 'x' can be referred to as '1', add it to '4x' to get '-5x'.
Sixth, divide both sides by '-5'.
Seventh, change the whole fraction into a negative.
Eighth, switch your sides.
![x = -\frac{6}{5}](https://tex.z-dn.net/?f=x%20%3D%20%20-%5Cfrac%7B6%7D%7B5%7D%20)
Answer as fraction:
![-\frac{6}{5}](https://tex.z-dn.net/?f=%20-%5Cfrac%7B6%7D%7B5%7D%20)
Answer as decimal: -1.2
Answer:
8.0000
Step-by-step explanation:
Answer:
ab = 2
Step-by-step explanation:
Given equations
ax² +ax + 2 = 0
x² + x + b = 0
root of both the equation
x= 1
then we can plug in x = 1 in both the equation
ax² +ax + 2 = 0 x² + x + b = 0
a*1² +a*1 + 2 = 0 1² + 1 + b = 0
a +a + 2 = 0 1 + 1 + b = 0
2a + 2 = 0 2 + b = 0
2a = - 2 b = -2
a = -2/2 = -1
Thus,
a = -1
b = -2
a*b = -1*-2 = 2
ab = 2
Answer:
12700 feet
Step-by-step explanation:
Do 5/8 of 20,320
Do 20320 divided by 8 which is 2540
Do 2540 times 5 which is 12700